(untitled) (INTERNATIONAL SEMINAR, 2025)
Background: Dental caries is still a major health problem in Indonesia, especially among children. Data shows that the prevalence of dental caries in Indonesia reaches 56.9% in children aged >3 years, which will have an impact on children’s health and quality of life. Purpose: To determine the effect of the ‘Ekarini’ education model on improving children’s knowledge and skills in brushing their teeth to maintain early childhood dental health through a structured educational approach based on children’s developmental needs. Methods: This study used an experimental design with a one-group pretest-posttest approach. The population in this study were children aged 3–6 years at the Quran Hadits Kindergarten in Jambi City. The sample was selected using purposive sampling, resulting in a sample size of 140 children. Finding: The results of this study showed a p-value of 0.000 <0.05, which means that there was a significant difference between the children’s knowledge before and after the intervention. Value: This study not only had an impact on improving children’s knowledge and skills in dental care, but also contained educational, character, and social values that are very important for the formation of a healthy and independent personality from an early age.